The Influence of Climatic Factors on Age‐Group‐Specific Malaria Burden in Western Kenya - Felix M. Pabon‐Rodriguez; George Ayodo (Public Health Challenges)
ABSTRACT Background Despite well‐documented relationships between climate and malaria transmission, there is a lack of information on how precipitation and temperature as climatic factors specifically impact malaria burden among different age groups in high‐transmission areas in Western Kenya. Current models often overlook the time‐lagged effects of climate variables, such as precipitation and temperature, on age‐group‐specific malaria burden. Methods This study utilized monthly malaria positivity data from three health centers, along with climate data from Western Kenya by applying Negative Binomial mixed effects models with both current and lagged climate variables. Interaction plots, analysis of deviance, and goodness‐of‐fit tests were used to assess the significance of some relationships or choose a model with a better fit. The Negative Binomial model was compared with the Poisson model and their zero‐inflated counterparts. Results The study revealed that the 2‐month lagged precipitation and temperature were significant predictors of malaria positivity, with older age groups showing higher susceptibility. Site‐to‐site and year‐to‐year variations were also identified as important sources of variation to be considered. Conclusions The study highlights the importance of considering both age‐specific vulnerability and climatic influences in malaria control strategies, suggesting the need for targeted interventions for malaria risk in age‐specific groups following the period of precipitation.